Persepsi Masyarakat Terhadap Dana Bantuan Langsung Tunai (BLT) dalam Meningkatkan Perekonomian Keluarga Menurut Perspektif Ekonomi Islam (Studi pada Masyarakat Kecamatan Glumpang Baro Kabupaten Pidie) - Safira, Leni; Amri, Khairul; Hafidhah (Yayasan Kawanad, 2024)
Direct Village Fund Cash Assistance (BLT-Dana Desa) is financial assistance to poor families in villages sourced from the Village Fund to reduce the impact of the COVID-19 pandemic in improving the family economy. This study aims to determine the process of distributing Cash Direct Assistance (BLT) and public perceptions of Cash Direct Assistance (BLT) funds in an effort to improve the family economy according to the perspective of Islamic economics in Glumpang Baro sub-district, Pidie district. This research is a quantitative research. The results of the study found that the dimensions of perceived benefits became the most important perceptions in improving the community's economy, then the dimensions of perceptions of justice and dimensions of perceptions of information disclosure and the dimensions of perception of the distribution process were in the last order. The results of the Man-Whitney test indicate that differences in age, occupation, marital status, education level and frequency of receiving BLT do not cause differences in people's perceptions in improving the family economy according to an Islamic economic perspective.